2015
DOI: 10.1016/j.ejrh.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of precipitation in the Upper Tennessee Valley

Abstract: a b s t r a c t Study region: Upper Tennessee River Basin, United States. Study focus: The temporal variation of precipitation in the Upper Tennessee River Basin was investigated by utilizing datasets from the Tennessee Valley Authority (TVA) rain gauge network consisting of 56 rain gauges , and the National Weather Service (NWS) analyzing mean areal precipitation values for 78 subbasins . The Mann-Kendall trend test, Mann-Kendall-Sneyers test, Yamamoto Method, and Morlet's wavelet were applied to reveal preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 46 publications
(50 reference statements)
1
32
0
Order By: Relevance
“…Of the two methods most commonly used, the parametric and nonparametric methods, the latter has been favored over the former [49]. Among the nonparametric methods, the Mann-Kendall (MK) statistical test [51,52] has been frequently used to quantify the significance of trends in time series [1,23,[45][46][47][48][49][50][53][54][55][56][57][58][59][60]. It is also widely used in environmental science because it is simple, robust, and can cope with missing values and values below a detection limit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the two methods most commonly used, the parametric and nonparametric methods, the latter has been favored over the former [49]. Among the nonparametric methods, the Mann-Kendall (MK) statistical test [51,52] has been frequently used to quantify the significance of trends in time series [1,23,[45][46][47][48][49][50][53][54][55][56][57][58][59][60]. It is also widely used in environmental science because it is simple, robust, and can cope with missing values and values below a detection limit.…”
Section: Discussionmentioning
confidence: 99%
“…An extension of the MK method, called the Sequential Mann-Kendall (SQMK) test, is widely used to detect the time (year) when a trend shows a shift (change in regime trend turning point) [1,20,47,49,56,58,60]. SQMK consists of sequential forward (u(t i )) and backward (u'(t i )) analyses of the MK test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important feature of the long-term changes is that they are not monotonic but rather fluctuate on a shorter temporal scale, similar to the temporal variation that [10] observed in North Carolina (USA) and [38] in the Upper Tennessee Valley (USA). Likewise, [12] showed this medium-term variation of the precipitation series in China and determined, from sequential MKS procedures and the moving average difference (mobile t-test), the occurrence of up to three jumps or breakpoints between 1960 and 2008. de la Casa and Nasello (2010) [5] observed a fluctuation of between 10 and 20 years in rainfall time series of Cordoba, Argentina, analyzed from the nonlinear method of partial slopes [20].…”
Section: Variation Of Rainy Days In Córdoba City (Bo) Río Cuarto (Rcmentioning
confidence: 88%
“…Similarly, Villafuerte et al (2014) [14] find that extreme rains in the Philippines exhibit spatially incoherent behavior, with mixed positive and negative trends even among neighboring weather stations. Also, assessing temporal variability of rainfall in the Upper Tennessee Valley, Jones et al (2015) [38] concluded that only 11% of the 78 sub-basins experienced statistically significant increasing or decreasing precipitation over a 50-year period. This reveals changes in the rainfall regime are not widespread in a region nor has the same sign necessarily, as was observed in central Argentina.…”
Section: Trend Change Analysismentioning
confidence: 99%